Bandwidth shapers unclog busy networks. - Cherry, S.M.
Loyola College uses a network management technique called bandwidth shaping to solve the campus network traffic problem. The technique ensures that important network activities, such as file transfers, e.g. e-mail, and Web searching, do not get slowed down by less important activities, such as downloading music and movies. Bandwidth shapers are dedicated computers placed between the local network and its connection to the Internet-the same point in the network as a firewall
Keywords: Internet; Loyola College; Web searching; Bandwidth shapers; Bandwidth shaping; Campus network traffic problem; E-mail.; File transfers; Firewall; Music downloading; Network management